Fabrication of SiC reticulated porous ceramics with multi-layered struts for porous media combustion. Issue 11 (15th August 2016) - Liang, Xiong; Li, Yawei; Liu, Jun; Sang, Shaobai; Chen, Yuanyuan; Li, Benwen; Aneziris, Christos G.
Abstract: Silicon carbide reticulated porous ceramics (SiC RPCs) with multi-layered struts were fabricated at 1450 °C by polymer sponge replica technique, followed by vacuum infiltration. The effect of additives (polycarboxylate, ammonium lignosulfonate and sodium carboxymethyl-cellulose) on the rheological behavior of silicon carbide slurry was firstly investigated, and then the slurry was coated on polyurethane open-cell sponge template. Furthermore, alumina slurry was adopted to fill up the hollow struts in vacuum infiltration process after the coated sponge was pre-treated at 850 °C. The results showed that the coating thickness on the struts and the microstructure in SiC RPCs were closely associated with the solid content of alumina slurry during vacuum infiltration. The typical multi-layered strut of SiC RPCs could be achieved after the infiltration of an alumina slurry containing 77 wt% solid content. The compressive strength and thermal shock resistance of the infiltrated specimens were significantly improved in comparison with those of non-infiltrated ones. The improvement was attributed to the in-situ formation of reaction-bonded multilayer struts in SiC RPCs, which were characterized by the exterior coating of aluminosilicate-corundum, middle part of mullite bonded SiC and interior zone of corundum.